Characterization of the sports injury in athletes from the department of Cauca with projection to National Sports Games - Villaquirán, Andrés Felipe; Portilla Dorado, Enmanuel; Vernaza, Paola (Universidad y Salud, 2016)
Objective: To characterize the sports injuries in athletes from the department of Cauca, that are getting prepared for their participation in the National Sport Games in 2015. Materials and methods: A cross-sectional descriptive study was carried out with the athletes from Cauca with projection to National Sport games, who were attended in the physiotherapy service of the Biomedicine Unit of Indeportes Cauca during December 2013 and July 2015. The information was collected through the socio-demographic and clinical characteristics file of the Biomedicine Unit of Indeportes Cauca. The variables studied were: age, sex, stratum, month of attention, practiced sport, injured area of the body, type of injury and medical diagnosis of remission. Results: The sport that presented more lesions was badminton with 100% of injured people, followed by Judo with 13.9%, indoor soccer with 12.1% and volleyball with 8.7%. The tendinopathies and ligament injuries occupied the first place of incidence with 50.6% of sports injuries, the most affected area was the lower limbs. Conclusions: The study documents the lesions each sport reports with the purpose of performing a program of prevention and follow-up to the injury, which will result in the performance of the leagues and the results of the sportsmen from Cauca.